Size Controlled Synthesis of Starch Nanoparticles by a Microemulsion Method - Pang, Suh Cem; Chin, Suk Fun; Aressa, Azman (Hindawi Publishing Corporation, 2014)
Controllable particles sizes of starch nanoparticles were synthesized via a precipitation in water-in-oil microemulsion approach. Microemulsion method offers the advantages of ultralow interfacial tension, large interfacial area, and being thermodynamically stable and affords monodispersed nanoparticles.The synthesis parameters such as stirring rates, ratios of oil/cosurfactant, oil phases, cosurfactants, and ratios of water/oil were found to affect the mean particle size of starch nanoparticles. Starch nanoparticles with mean particles sizes of 109 nm were synthesized by direct nanoprecipitation method, whereas by using precipitation in microemulsion approach, starch nanoparticles with smaller mean particles sizes of 83 nm were obtained.